A manipulative study of macroinvertebrate grazers in Hong Kong streams: do snails compete with insects?. (13th August 2013) - Yeung, Alex C. Y.; Dudgeon, David
Summary: Sulcospira hainanensis (Pachychilidae) is the most abundant snail in Hong Kong streams. It constitutes about 1% of total benthic macroinvertebrate abundance but, because of its relatively large size, can comprise over one‐third of standing biomass. This snail may have the potential to depress periphytic algae and thereby compete for food with insect grazers. Possible competitive interactions were investigated by manipulating snail densities in 4 streams under different shading conditions (2 shaded, 2 unshaded). Since previous work in Hong Kong streams indicated that algal standing stocks were depleted by wet‐season spates, manipulations were carried out during both the wet and dry seasons to investigate the extent of variability in interaction intensity. Insect colonisation on artificial substrata (tiles) was compared between treatments where wire mesh barriers limited snail access, and under control conditions of natural snail densities. The exclusion treatment reduced snail densities by about 30–50% relative to controls during both seasons. Algal densities were lower during the wet season in two streams, probably reflecting spate‐induced disturbance, but snail densities remained relatively stable throughout the study. Strong effects of S. hainanensis on algae and insects were observed during the dry season, with higher algal biomass and insect densities (especially mayflies) in snail‐exclusion treatments. Differences between treatments during the wet season were generally minor. Snails depressed algae more severely in shaded streams, but this did not result in greater increases in insect abundance in snail‐exclusion treatments. Evidently snails did exert competitive effects on insects, but spate‐induced disturbance during the wet season appeared to override this biotic interaction, in agreement with predictions of the harsh‐benign hypothesis. Competition intensity was unaffected by shading conditions, perhaps because other environmental factors moderated interaction intensity in shaded streams.